Pengaruh Kepemimpinan Transformasional terhadap Kepuasan Kerja pada ASN Sekretariat Daerah Kantor Walikota Kota Bukittinggi - Alhanif, Muhammad Iqbal; Guspa, Anindra (TSAQOFAH, 2025)
In today's work environment, there are many problems such as dissatisfaction and even discomfort in carrying out work that cause quitting work or resigning. This study aims to determine the influence of transformational leadership on job satisfaction in civil servants at the Regional Secretariat of the Bukittinggi City Mayor's Office. This study uses a quantitative method. The subjects in this study are 118 civil servants of the Regional Secretariat of the Bukittinggi City Mayor's Office. The data collection method in this study uses a job satisfaction scale with a reliability of 0.943 and a transformational leadership scale with a reliability of 0.910. Data analysis using a simple linear regression test with the help of a program The Statistical Package for Sciences (SPSS) 26.0 for windows obtained the results of the hypothesis test with a regression coefficient value of 0.245 with a significance value of P of 0.000 (P < 0.05). This shows that there is a significant positive influence between transformational leadership on job satisfaction in civil servants at the regional secretariat of the Bukittinggi City Mayor's Office, meaning that the higher the transformational leadership, the higher the job satisfaction felt by workers. Overall, the results show that the majority of civil servants in the Regional Secretariat of the Bukittinggi City Mayor's Office have transformational leadership and high job satisfaction.